MORE SLAVE WOMEN, MORE LEWDNESS: Freedom and Honor in Rabbinic Constructions of Female Sexuality - Labovitz, Gail (Journal of feminist studies in religion, 2012)
Rabbinic texts legislate for a slave society, biblical law incorporates slaveholding, slavery is well documented within the two primary cultures in which rabbinic Judaism took shape, and multiple sources of evidence demonstrate that Jews could be slaveholders or held as slaves. Yet most scholars now agree that it is problematic to read the prescriptions of rabbinic slave law as straightforward representations of actual social practices. This difficulty has had the effect of making the issues that follow from recognizing rabbinic culture as a slave culture not fully visible. Nonetheless, the permeating presence of slavery in these texts suggests a critical need for a fundamental reconsideration of rabbinic rhetoric in this area. This article focuses on the intersection of slavery and the construction of female sexuality in rabbinic thought. This example demonstrates the difference that foregrounding the rabbinic acceptance of slavery can make to a discussion of Jewish marriage and sexual ethics today. [PUBLICATION ABSTRACT]